PENGARUH SIKAP KARYAWAN TERHADAP KOMITMEN ORGANISASI - Satria, Rd. Okky; Komara, Anton Tirta; Suzanto, Boy (Majalah Bisnis & IPTEK, 2021)
This study aims to determine the effect of employee attitudes componentsconsisting of affective, cognitive and behavioral of employees towards organizational commitment. Hypothetical testing was used a sample tested employees in one of the Tax Service Office in Bandung with 95 employees for samples. Sampling techniques used simple random sampling of existing populations. Data analysis techniques was using path analysis. This research method is included in the survey method category. The results of the study prove that there is an influence of attitudes towards employee commitment of 72.2% while the remaining 27.8% is influenced by another factors that not examined in this study. Keywords: affective, cognitive, conative, organizational commitment